Perancangan Mesin Dewatering Untuk Pemisah Sludge Pada Kolam IPAL Pabrik Kelapa Sawit - Suherman Suherman; Susri Mizhar; Muharnif Muharnif; Ilmi Ilmi; Muhammad Subhan Ananda Tanjung (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Sludge generated from the wastewater treatment plant of palm oil mills contains a very high moisture content, which increases volume, handling costs, and poses a potential risk of environmental pollution if not properly managed. One of the main challenges encountered is the lack of a simple, economical small-scale dewatering machine that is suitable for the characteristics of sludge produced by palm oil mill wastewater treatment systems. This study aims to design and fabricate a dewatering machine to separate sludge from water in the wastewater treatment ponds of a palm oil mill. The research method involved designing the machine using SOLIDWORKS software, performing technical calculations of the main components such as motor power, shaft dimensions, belt transmission, and bearings, followed by fabrication and assembly processes. The performance of the machine was then evaluated based on its ability to separate sludge and water. The results indicate that the designed dewatering machine has a capacity of 200 litres per hour with a motor power of 1 HP; however, its performance has not yet reached optimal conditions, as part of the sludge remains attached to the screen, thereby increasing the motor load and hindering the movement of the screw. The findings of this study suggest that the dewatering machine design has the potential for further development through optimisation of the screw geometry and filtration system in order to improve sludge water separation efficiency in palm oil mill wastewater treatment plants.